Spatio-temporal distribution of the fish Synodontis schall (Teleostei: Mochokidae) in Asa lake, Ilorin, Nigeria - P. A Araoye (Revista de Biología Tropical, 1999)
Spatio-temporal distribution of Synodontis schall in Asa lake was studied for 24 months (March 1991 to February 1993). Distribution of individual was: 28.40 % (surface), 35.60 % (shore), and 36.0 % (bottom). Catches within the habitat were not significantly different. Similarly catches within the habitats during the periods of wet (May to October) and dry (November to April) seasons were not significantly different. There was seasonal occurrence of the fish at the bottom because the catches from this habitat in October (4.80 to 9.10 %) and November (0.00 to 8.70 %), corresponding with the period of flood and high water levels, were relatively low due to feeding and reproductive phenomena. Although catch was inversely proportional to the water levels, this was not significant in this experimental gill net catches. Synodontis schall was caught throughout the sampling period indicating its successful adaptation within the environment due to low predation and its diverse feeding habits.